Eficiência do guarda-redes de andebol nos últimos Campeonatos do Mundo para homens e mulheres] - Gómez-López, M.; Sánchez, S. A.; López-Triviño, J.; Antúnez, A. (Revista Ciencia del Deporte, 2021)
The performance of goalkeepers can predict the final ranking of teams in tournaments. The purpose of the study was to examine the percentages of saves by goalkeepers from 15 national teams, according to the position in the field from which the shot was taken and according to the location of the shot in the goal, and to analyze the differences according to the goalkeeper's gender. A documentary study was carried out based on the data collected by the International Handball Federation of 227 games of 30 national teams that participated in the last absolute world championships of both men's (Germany-Denmark 2019) and women's (Germany 2017) handball. The results showed that the highest percentage of both men's and women's saves was obtained from shots taken from 9 meters and to the central and middle zone of the goal, and the lowest was obtained from throws in counterattack and to the lower and lateral zones of the goal. Finally, the women obtained the highest percentage of stops both before the throws from the different locations in the field and in the different areas of the goal.